Cell Secretome: Basic Insights and Therapeutic Opportunities for CNS Disorders - Andreia G. Pinho; Jorge R. Cibrão; Nuno A. Silva; Susana Monteiro; António J. Salgado (MDPI AG, 2020)
Transplantation of stem cells, in particular mesenchymal stem cells (MSCs), stands as a promising therapy for trauma, stroke or neurodegenerative conditions such as spinal cord or traumatic brain injuries (SCI or TBI), ischemic stroke (IS), or Parkinson’s disease (PD). Over the last few years, cell transplantation-based approaches have started to focus on the use of cell byproducts, with a strong emphasis on cell secretome. Having this in mind, the present review discusses the current state of the art of secretome-based therapy applications in different central nervous system (CNS) pathologies. For this purpose, the following topics are discussed: (1) What are the main cell secretome sources, composition, and associated collection techniques; (2) Possible differences of the therapeutic potential of the protein and vesicular fraction of the secretome; and (3) Impact of the cell secretome on CNS-related problems such as SCI, TBI, IS, and PD. With this, we aim to clarify some of the main questions that currently exist in the field of secretome-based therapies and consequently gain new knowledge that may help in the clinical application of secretome in CNS disorders.